Prevalence and Predictors of COPD Among Adults Attending Primary Care Clinics in Pakistan - Mohammad Umaid Sohail, Arsalna Sheikh, Umair Anwar, Muhammad Azhar Khan, Shabir Ahmad, Mir Abdul Qadir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Chronic obstructive pulmonary disease (COPD) is an under-recognized cause of morbidity and mortality in Pakistan where major risk factors—tobacco use, household biomass exposure and ambient air pollution—remain prevalent. This cross-sectional study estimated the prevalence of spirometry-confirmed COPD and identified independent predictors among adults attending primary care clinics.